At the Interface Between Paradigms: English Mental Capacity Law and the CRPD - Bartlett, Peter (Frontiers in Psychiatry, 2020)
The United Nations Convention on the Rights of Persons with Disabilities (CRPD) is rightly seen as a break from the past in mental capacity law. At the same time, implementation will occur in the specific existing legal and administrative contexts of each State. This article uses English mental capacity law to explore these issues. The English Mental Capacity Act 2005 (MCA) can be considered the best of the ‘old’ paradigm. The article argues that there are continuities between it and a CRPD-compliant approach. These continuities should be built upon. Further, the implementation of the MCA is still in recent memory. The lessons of that implementation will have considerable application to moves towards CRPD compliance. CRPD compliance is not just about specialist stator guardianship régimes. It is also about a myriad of law, currently capacity based, located in specific legal areas such as contract, wills and succession, and criminal law. Reform in these areas will involve not just disability law, but successful integration into those other legal areas, a matter requiring the involvement of those knowledgeable in those other areas. Since change in these areas will involve the removal of disability as a gateway criterion, they will affect the public as a whole, and the thus determination of the degree and sort of intervention that the broader public will consider appropriate.